ANALISIS PRODUKSI DAN PEMASARAN JAGUNG MANIS DI KELURAHAN KLAMALU DISTRIK MARIAT KABUPATEN SORONG PROVINSI PAPUA BARAT - Wiwin Hotimah; Kunto Wibowo; Ishak Suwardi (Sosio Agri Papua, 2020)
Agriculture is the main sector of Indonesian people's livelihoods. The agricultural sector is able to contribute directly to economic growth and the welfare of farm households. And is one of the pillars of the national economy. This means that the agricultural sector plays an important role and should be a driver of state economic activity. Based on 2005 BPS data, the population working in the agricultural sector numbered around 41,309,776 people or 39.02 percent of the total population of productive age, while the remaining 60.98 percent was spread in various sectors outside agriculture. This study aims to (1) Know the sweet corn production produced by farmers (2) Know the factors that influence the amount of sweet corn production (3) Know the marketing of sweet corn from farmers. The method used in this research is descriptive method with survey techniques. The sampling method in this study was carried out by simple random sampling (simple randon sampling) on corn farmers. based on research results obtained. The average production produced from sweet corn farming in Klamalu Village, Mariat District, Sorong Regency is 1,827 kg / ha in one planting season, with an average land area of 0.39 Ha. The production has not reached maximum results because it has not been matched with the right cultural technology. Based on multiple linear regression analysis, it can be seen that the most influential on sweet corn production variables is the land variable with a regression coefficient of 3,492,641 (31 percent). Work outflow variable has positive and significant effect with regression coefficient value of -0.013 (39 percent). While the variable capital costs have a negative and significant effect on production. This can be indicated by a significant value (P value) of 0,000 which is smaller than 0.05. In testing hypotheses using the F test (together or simultaneously) it can be explained that the five variables namely price (X1), production costs (X2), land (X3), production (X4), transportation costs (X5) and competitor prices (X6) together affect the bid (Y). This is indicated from the calculated F value of 11.186 with a significance number (P Value) of 0.047. The coefficient of determination (R2) produced is 0.64. This means that 64 percent of the change in the supply variable (Y) can be explained by changes in the land variable (X1), capital (X2), work flow (X3), together, while the remaining 36 percent is explained by other variables not available in this research. There are only 2 sweet corn trading channels in the Kelurahan klamalu Mariat District, namely: Consumer Farmers; Pedagag Farmers Consumer Retailers. The average profit received by farmers is greater than Rp. 21,884,309, compared to farmers who sell sweet corn products at retailers only at Rp. 568,167. Based on the calculation results, the efficiency of the trading system obtained by retailers is greater than 100% which is 1,170%. This shows that the trading agency is efficient. Based on the results of the study, there are several obstacles faced by farmers in the Klamalu District of Mariat District, Namely: The capital owned by farmers is limited, 2. Availability of fertilizer which is not always available, 3. The absence of marketing institutions in the form of cooperatives and traders, 4. Marketing areas that are limited.